ERROR-CONTROL CODING OF ADS-B MESSAGES FOR IRIDIUM SATELLITES - Kharchenko, Volodymyr; Barabanov, Yurii; Grekhov, Andrii; Bogunenko, Mykola; Rudnyk, Julia (Proceedings of National Aviation University, 2014)
For modelling of ADS-B messages transmitting on the base of low-orbit satellite constellation Іrіdіum the model of a communication channel “Aircraft - Satellite - Ground Station” was built using MATLAB Sіmulіnk. This model allowed to investigate dependences of the Bit Error Rate on a type of signal coding/decoding, ratio Eb/N0 and satellite repeater gain